2002
DOI: 10.1097/00007632-200201150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Backpacks on! Schoolchildren’s Perceptions of Load, Associations With Back Pain and Factors Determining the Load

Abstract: Daily backpack carrying is a frequent cause of discomfort for schoolchildren. There is an association between this load and back pain, although the relationship is not direct. The results suggest the existence of personal physical and psychological factors that need to be investigated. Reduction of the daily backpack load borne by schoolchildren is recommended both on the basis of the current results and because it exceeds, proportionally, the legal load limits set for adults. All the different parties involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
160
2
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(199 citation statements)
references
References 16 publications
15
160
2
16
Order By: Relevance
“…Young people commonly use backpacks as they are an effective and most economical way of carrying weight, however, it has been proposed they can also be a significant contributing risk factor for dis-comfort, fatigue, muscle soreness and musculoskeletal pain especially low back pain [9,29,[47][48][49]57]. It has been speculated that backpacks may cause problems not only for the developing skeletal system but also for a mature spine as a developed spine is also sensitive to load [41,45]. Moreover, experiencing back pain in childhood is a concern as it may lead to more common and severe issues later in life [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people commonly use backpacks as they are an effective and most economical way of carrying weight, however, it has been proposed they can also be a significant contributing risk factor for dis-comfort, fatigue, muscle soreness and musculoskeletal pain especially low back pain [9,29,[47][48][49]57]. It has been speculated that backpacks may cause problems not only for the developing skeletal system but also for a mature spine as a developed spine is also sensitive to load [41,45]. Moreover, experiencing back pain in childhood is a concern as it may lead to more common and severe issues later in life [41].…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that backpacks may cause problems not only for the developing skeletal system but also for a mature spine as a developed spine is also sensitive to load [41,45]. Moreover, experiencing back pain in childhood is a concern as it may lead to more common and severe issues later in life [41].…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [10] recommended a backpack weight limit of 10 % on the basis of significant changes in forward trunk lean and blood pressure recovery time of 10-year-old boys walking on a treadmill. Cavallo et al [11] found that over a quarter of the female students in a fourth grade group carried a backpack of greater than 15 % BW, while Negrini and Carabalona [7] reported a mean backpack load of over 20 % BW. The daily loads applied by schoolbags are of particular concern in patients with AIS as abnormal external loading has been suggested as one of the possible factors that may affect the growth of the spine and exacerbate the scoliotic deformity [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the loads carried daily in schoolbags are relatively high with respect to the child's body weight, and have generally been found to exceed the recommended BW limits. Carrying an overweight backpack makes a child unable to maintain a proper standing posture [7] and may present loading rate asymmetries, which are the most sensitive indicators of gait dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%
“…Os escolares referiram a preferência de carregar a mochila nas costas com as duas alças no mesmo ombro. O transporte da mochila também foi estudado por Negrini et al 23 que relatam que carregar a mochila diariamente é causa freqüente de desconforto entre os escolares. Korovessis et al 24 mostraram a correlação com a lombalgia quando a mochila foi transportada com as duas alças no mesmo ombro.…”
Section: Discussionunclassified